The Effect of Giving Rewards and Punishment on the Learning Motivation of Class V Students at SDN 101769 Tembung - Didenickri Padang; Masytoh Rangkuti; Reni Afriani Samosir; Yemima Xaveria Maran Siregar; Laurensia M. Perangin Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Motivation has an important role so that the learning process in education can run well. This study aims to determine the effect of reward and punishment on the learning motivation of fifth grade students at SDN 101769 Tembung. This type of research used is quantitative research. The form of research used is descriptive survey research. The results showed that there was a positive and significant influence between giving rewards and punishments on the learning motivation of Class V students at SDN 101769 Tembung. The effect of reward and punishment on student learning motivation has an r coefficient of 0.633. Then, the magnitude of the influence of reward and punishment on student motivation is 40% which is obtained through the analysis of the coefficient of determination. Meanwhile, 60% which influences student learning motivation comes from other factors that are not included in this study.